Financial Literacy and Spending Patterns of Millennials and Generation Z in Pokhara, Nepal - Chhetri, Shanti Devi; Bhandari, Sushanti (Journal of Business and Management, 2025)
Background: The study focus on financial literacy and spending behavior among Millennials (28-44) and Generation Z (18-27) in Pokhara, Nepal, in the aspect of the high rate digitalization of financial systems. Although there is an increasing complexity in financial decision making among the younger demographics, there is a dearth of literature on the same related to the Nepalese context. Objectives/Design/Methodology/Approach: The study is based on the Theory of Planned Behavior and Human Capital Theory and it examines how financial competencies, self-efficacy and literacy interact to promote prudent financial behaviors. The study involved 250 participants collected using structured surveys using a quantitative and cross-sectional method. Partial Least Squares Structural Equation Modelling (PLS-SEM) was used to examine the direct and mediating relationships between variables. Results: The results show that Millennials exhibit better financial ability, self-efficacy, literacy and disciplined spending than Generation Z. Millennials showed better abilities in investment strategies, budgeting processes and dealings with financial data, Gen Z used digital tools much more often but were less skilled in advanced financial system. The structural model also recognised that financial literacy mediates the association between financial skills, self-efficacy and spending behavior with financial skills having the highest indirect impact on responsible expenditure through literacy followed by a small but significant role of self-efficacy. Conclusion: The study found the differences in financial literacy and spending patterns between Millennials and Generation Z. These generational variations can be further studied to improve financial stability and prosperity in the changing economy of Nepal.